(untitled) (KIUT Publication, 2025)
This article analyzes the factors through which global climate change affects human health, particularly contributing to the onset of disability. The study highlights how negative environmental changes, extreme climate events, and ecological degradation pose risks to the health of socially vulnerable groups, especially women, children, and persons with disabilities. Recommendations and proposals aimed at preventing these issues are provided.